Transformation of Central and Eastern European Countries from the Perspective of New Institutional Economics - Swatek, Małgorzata (Ekonomika, 2008)
Economic transformation in Central and Eastern European countries is a very complex process widely discussed in the literature on the subject. It has also become the subject of research and analyses of New Institutional Economics which pays attention to new aspects of transformation. From the NIE perspective, transformation is a long-lasting process of changes of formal institutions, especially property rights and contracts, and informal institutions, such as ethical standards, conventions, religious beliefs and mentality of society. The success of the transformation depends on the degree to which new formal rules correspond to informal rules existing in society. The assessment of the quality of Central and Eastern European countries leaves a lot to be desired; the highest level was achieved by the EU member states, whereas the republics of the former USSR are in the worst situation. The underlying causes of such diversified results of political transformations are disparate historical traditions connected with the market economy and unequal preparation of societies to exist both in the free market conditions and in the diversified political, social and economic situation.The improvement of governing quality is a priority in post-communist countries. Achieving a positive institutional effect requires much time and consistent actions, but from the time perspective it is crucial in order to enjoy economic success.